Features of Authenticity Development in Future Psychologists - Radchuk, Halyna; Adamska, Z; Oliinyk, Maria (My University, 2019)
The article addresses an acute problem of contemporary psychology - theoretical and empirical study of authenticity development of psychology students. The articles describes awareness of authenticity of psychologists as a professionally important integral personal characteristic based on a theoretical analysis of existing approaches in Ukrainian and foreign psychology. This construct implies respectful attention and fair treatment of oneself and own feelings, recognition of own value which makes clients feel that they are understood and accepted. This helps clients understand and accept their own feelings, learn to trust themselves, find strength to realize their own uniqueness, and acquire the ability for self-development. The Authenticity Scale methodology by Alex M. Wood, P. Alex Linley, J. Maltby, M. Baliousis and S. Joseph was used in an empirical research of the authenticity development features in future psychologists – Bachelor's degree graduates (adaptation of S. Nartova-Bochaver, V. Bardadimova). The basis for this methodology is personality focused understanding of authenticity, which has three levels: self-alienation, authentic living, and acceptance of external influence. Quantitative and qualitative analysis of the obtained results show that most students-future psychologists have high level of awareness of their authenticity. At the same time, a majority of students show dependence from thoughts, evaluations and expectations of their environment, as well as insufficient level of understanding of themselves and their inner world, which, in turn, can lead to self-alienation. There is also correlation between empirical indicators on the Authenticity Scale and respondents’ age. It has been established that with age the level of authenticity awareness, the ability to uphold own beliefs and live in accordance with own values gradually decreases
Keywords: authenticity; authenticity of a psychologist; authenticity of self-expression; acceptance of external influences; self-alienation